Penerapan Model Project Based Learning Untuk Memaksimalkan Hasil Belajar Matematika Pecahan Siswa Kelas IV - Nina, Nina; Sapriati, Amalia (Peneliti.net, 2025)
This study aims to improve the learning outcomes of fourth grade students in fraction mathematics at SD IT Al Jadid through the implementation of the Project Based Learning (PJBL) learning model. The method used in this study is a qualitative approach with direct observation and analysis of student learning outcomes. The learning process was carried out for four weeks, involving 20 students who were divided into groups to complete a fraction modeling project. The results showed that the use of various learning resources, including multimedia, successfully increased students' interest and understanding. Formative and summative assessments showed a significant increase in learning outcomes, with many students achieving scores above the Minimum Completion Criteria (KKM). Although there were obstacles such as anxiety during presentations and lack of knowledge about local wisdom, the solutions implemented, such as emotional support and discussion sessions, successfully addressed these problems. This study concluded that the PJBL model was effective in improving fraction mathematics learning outcomes and encouraging students' social skills. Suggested follow-ups include improving material preparation, presentation training, and integrating local cultural elements into learning. Thus, the implementation of the PJBL model not only improves academic outcomes, but also builds self-confidence and collaboration between students, which are very important in a holistic learning process. This research is expected to be a reference for educators in implementing innovative and effective learning methods.